2015
DOI: 10.1212/wnl.0000000000001234
|View full text |Cite
|
Sign up to set email alerts
|

Gamma oscillations precede interictal epileptiform spikes in the seizure onset zone

Abstract: Objective: To investigate the generation, spectral characteristics, and potential clinical significance of brain activity preceding interictal epileptiform spike discharges (IEDs) recorded with intracranial EEG.Methods: Seventeen adult patients with drug-resistant temporal lobe epilepsy were implanted with intracranial electrodes as part of their evaluation for epilepsy surgery. IEDs detected on clinical macro-and research microelectrodes were analyzed using time-frequency spectral analysis.Results: Gamma freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 11 publications
6
82
0
Order By: Relevance
“…The onset of ripple 28 and gamma 29 oscillations can precede inter-ictal epileptiform discharges, while gamma can occur after inter-ictal discharges as well as fast ripples, i.e. fast ripple tail gamma 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The onset of ripple 28 and gamma 29 oscillations can precede inter-ictal epileptiform discharges, while gamma can occur after inter-ictal discharges as well as fast ripples, i.e. fast ripple tail gamma 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fast oscillations in the gamma and low ripple range (30-100 Hz) have been found to precede interictal epileptiform spike discharges (IEDs), and these so called gamma-IEDs are strongly associated with the SOZ in TLE [31]. Although HFOs and spikes are closely related, their dynamics differ.…”
Section: High-frequency Oscillationsmentioning
confidence: 99%
“…The association between pHFOs and interictal epileptiform discharges (IEDs) was investigated by various studies [21,22,46,56]. Wang et al, [21] classified neocortical ripples into two subtypes: type I ripples superimposed on an IED, and type II ripples independent of any epileptiform discharges.…”
Section: Association Of Phfos With Interictal Epileptiform Dischargesmentioning
confidence: 99%
“…Ren et al, [22] studied the gamma HFOs that precede IEDs and found a strong association between seizure generating brain and gamma HFOs that preceded IEDs, in contrast to IEDs alone. They proposed the gamma HFOs proceeding IEDs may be useful for mapping pathological brain regions.…”
Section: Association Of Phfos With Interictal Epileptiform Dischargesmentioning
confidence: 99%
See 1 more Smart Citation